Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1969
DOI: 10.1088/0026-1394/5/2/004
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Expansion of Fused Quartz

Abstract: Results of a series of observations on the linear thermal expansion coefficient of transparent fused quartz are given in the temperature range of 300 "C to 1065 "C, with particular attention being given to the region of 1000 O C .The experiments are carried out by the comparator method. The ten specimens, which could conveniently be classified into three types, were supplied by the Thermal Syndicate Ltd., England and by three manufacturers, the Toshiba Ceramics Ltd., the Nippon Sekiei Garasu Ltd. and the Kimmo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
37
1

Year Published

1978
1978
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 71 publications
(41 citation statements)
references
References 6 publications
0
37
1
Order By: Relevance
“…This property, combined with adequate strength, excellent corrosion resistance, ablation resistance, and excellent electrical and dielectric properties, make fused quartz the material of choice for a wide range of applications, including radomes, radar windows, combat and space vehicles [62], vacuum windows [63,64], boats and crucibles for high temperature material handling and fabrication, and high power lamp tubing. Due to the high purity of fused quartz, its properties are very sensitive to small changes in composition and thermal history [65]. The hydroxyl content of fused quartz is one of the major impurities that affects its properties.…”
Section: Fused Quartzmentioning
confidence: 99%
See 2 more Smart Citations
“…This property, combined with adequate strength, excellent corrosion resistance, ablation resistance, and excellent electrical and dielectric properties, make fused quartz the material of choice for a wide range of applications, including radomes, radar windows, combat and space vehicles [62], vacuum windows [63,64], boats and crucibles for high temperature material handling and fabrication, and high power lamp tubing. Due to the high purity of fused quartz, its properties are very sensitive to small changes in composition and thermal history [65]. The hydroxyl content of fused quartz is one of the major impurities that affects its properties.…”
Section: Fused Quartzmentioning
confidence: 99%
“…The COTE of many but not all specimens of vitreous silica reported are very slightly anisotropic [99]. Due to the high purity of fused quartz, its thermal expansion coefficient can be significantly affected by small differences in composition [65]. The previous thermal history of a sample of fused quartz can greatly affect its measured thermal expansion coefficient, with significant differences noted between un-annealed and fully annealed samples [65,99].…”
Section: Thermal Expansion Coefficientmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently some experimental results [27] showed that the CTE ¼ 3.5 ppmK À1 from 30 C to 370 C for ALD-Al 2 O 3 thin film. Considering the linear CTE values of silicon substrate ¼ 2.6-4.3 ppmK À1 from 27 C to 700 C [28] and the linear CTE of quartz substrate ¼ 0.57-0.50 ppmK À1 from 300 C to 700 C [29], it is obvious that the silicon substrate matches the ALD-Al 2 O 3 film much better than the quartz substrate in thermal expansion, but the ALD-Al 2 O 3 film expands due to thermal expansion before the crystallisation. This may be one of the reasons for the fact that the pimples on quartz substrate (Figure 1(d)) are bigger than that on silicon substrate (Figure 1(b)) after the annealing treatment in hydrogen environment at high temperature for 10 min.…”
Section: Resultsmentioning
confidence: 99%
“…It is relative when the difference in length of two gauges is measured (one of which is the sample and the other is an initial gauge with known CLTE and length). Advanced comparator dilatometers have been built at a number of metrological institutes in various countries [7][8][9] and can measure elongation with a mean square deviation on the order of 0.6 μm.…”
mentioning
confidence: 99%